2014
DOI: 10.1016/j.acra.2013.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Is Higher Lactate an Indicator of Tumor Metastatic Risk? A Pilot MRS Study Using Hyperpolarized 13C-Pyruvate

Abstract: Rationale and Objectives Cancer cells generate more lactate than normal cells under aerobic and hypoxic conditions – exhibiting the so-called Warburg effect. However, the relationship between the Warburg effect and tumor metastatic potential remains controversial. We intend to investigate whether the higher lactate reflects higher tumor metastatic potential. Materials and Methods We employed hyperpolarized 13C-pyruvate magnetic resonance spectroscopy (MRS) to compare lactate 13C-labeling in vivo in breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…(16, 48, 49) Xu et al utilized this imaging platform to differentiate between cell lines with high and low metastatic potential. (15) Thind et al demonstrated that HP-MRI can be used to detect acute normal tissue radiation toxicity in a lung model. (50)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(16, 48, 49) Xu et al utilized this imaging platform to differentiate between cell lines with high and low metastatic potential. (15) Thind et al demonstrated that HP-MRI can be used to detect acute normal tissue radiation toxicity in a lung model. (50)…”
Section: Discussionmentioning
confidence: 99%
“…(14) On the basis of this and other promising pre-clinical data, Le et al conducted a potentially paradigm changing clinical trial, testing the potential of tumor lactate levels to predict treatment response in head and neck tumors. (15, 16) Unfortunately, data generated by this trial failed to demonstrate a correlation between proton magnetic resonance spectroscopic measurements of lactate signal intensity and clinical outcomes. (16)…”
Section: Introductionmentioning
confidence: 99%
“…Different investigations on animals have confirmed that the real‐time measurement of the conversion of pyruvate to lactate and alanine is particularly high in tumor tissue with high lactate dehydrogenase (LDH) activity and abundant membrane transporters of monocarboxylates. Thereby, HP MRI can allow a differentiation of benign and malignant tissue and has potential in the assessment of cancer progression . Recently, other promising novel probes for redox ( 13 C dehydroascorbate), necrosis ( 13 C fumarate), and glutamine metabolism ( 13 C glutamine) have been studied to investigate other metabolic pathways .…”
Section: Emerging Mri Parametersmentioning
confidence: 99%
“…[19][20][21][22][23][24][25] Furthermore, several studies have suggested that elevated LDH levels are correlated with radio/chemoresistance in several malignancies. LDH is essential for anaerobic glycolysis and converts pyruvate to lactate reversibly.…”
Section: Sclcmentioning
confidence: 99%